Method Sequence and Dominance in Mixed Methods Research: A Case Study of the Social Acceptance of Wind Energy Literature. Issue 1 (3rd April 2019) - Walker, Chad; Baxter, Jamie
As more researchers have considered the use of mixed methods, writings have moved away from debates about epistemological incompatibilities and now focus on the (potential) value of increased understanding that comes from combining qualitative and quantitative approaches. Yet, as the level of integration can vary substantially, some designs are said to allow one method or the other to dominate. Although there may be sound reasoning for intentionally allowing one method to dominate, here we investigate one literature as a moment to reflect why, and on the degree to which mixed methods sequence is so bound up with methodological dominance, that calling such studies "mixed" may seem misleading. Like the history of social science more generally, it is quantitative research that is typically given more weight in these studies and academics have noted a few reasons why this may be the case. Few have investigated how research design—and more specifically method sequence—may impact method dominance. Using an emerging mixed methods literature surrounding the social acceptance of wind energy ( N = 34), we study the relationship between the timing of each method (i.e., sequence) and method dominance to see whether qualitative methods in particular are marginalized. Through our Dominance in Mixed Methods Assessment model, we provide evidence that indeed qualitative methods are marginalized and this may be associated with method sequence and other design elements. Moreover, some authors focus solely on one method, giving pause to caution both writers and readers about the use of the term "mixed methods." The analytical approach is detailed enough to be replicated and detect whether these patterns are repeated in other research domains.